Mechanistic understanding of lodging in spring wheat (Triticum aestivum): An Indian perspective - BAINSLA, NARESH KUMAR; YADAV, RAJBIR; SHARMA, RAM KUMAR; SHARMA, AMBRISH; GAIKWAD, KIRAN B; KUMAR, AMIT; SINGH, VIKRAM; VYAS, PRITESH; SHARMA, AMBIKA (The Indian Journal of Agricultural Sciences, 2018)
Lodging in modern spring wheat (Triticum aestivum L.) varieties is largely overlooked in India. There is scanty information available in literature for Indian condition regarding the extent, distribution, direct and indirect losses caused by the lodging. Little work has been done on this problem post green revolution period in India. Introduction of dwarfing genes and development of semi-dwarf varieties has resulted in quantum yield gains during 1970-80. After this period till recent years the progress in yield gains are slowed down mainly due to plant architecture of modern varieties not supporting heavier heads inducing lodging. Therefore, the higher potential of genotypes could not be realized to full extent at field level and varieties promising consistent yield level of six tonnes /ha or more are lacking. The complex phenotyping strategies and models designed by the workers working on the problem elsewhere are further impeding the progress as these are not much helpful at field level under Indian conditions. The currentÂ paper takes into the consideration the mechanistic approach to understand the problem and correlate the facts and findings of universal nature to design the strategies to manage the lodging through different approaches much suitedÂ to Indian conditions.